A Bibliometric Analysis of Global Trends in Sustainability Accounting Research - Harahap, M Ikhwan Razzak (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
Purpose: This study aims to examine the evolution of sustainability accounting research from 1996 to 2025 using bibliometric techniques. It investigates how scholarly attention has shifted from early sustainability concepts toward standardized reporting frameworks, governance mechanisms, and performance-oriented sustainability practices. Research Design and Methodology: The study employs a bibliometric approach using keyword frequency analysis, trend analysis, co-occurrence network mapping, thematic evolution, and factorial (MCA) analysis. Data were retrieved from Web of Science and analyzed to identify dominant themes, structural linkages, and the conceptual progression of sustainability accounting. Findings and Discussion: Results show that research has evolved from broad sustainability and CSR concepts toward integrated reporting, ESG, carbon accounting, and governance-driven disclosures. Word frequency trends highlight the rise of sustainability reporting, ESG, GRI, and environmental management accounting. The thematic evolution map further confirms a shift from early conceptual themes toward standardized and regulation-driven sustainability reporting. Implications: These findings indicate that sustainability accounting has matured into a strategic, regulation-oriented field. The results emphasize the need for stronger reporting standards, enhanced assurance practices, and greater integration between sustainability information and financial decision-making.